A novel bioassay for the monitoring of carcinoembryonic antigen in human biofluid using polymeric interface and immunosensing method. Issue 10 (17th April 2020) - Moradkhani, Mahbubeh; Farshchi, Fatemeh; Hasanzadeh, Mohammad; Mokhtarzadeh, Ahad
Abstract: Carcinoembryonic antigen (CEA) is a member of a family of cell surface glycoproteins. Recognition of CEA is needed to monitor the physiological status of the patient for treatment and also it is important to assess the severity of the disease. In this work, we reported a novel sandwich‐type electrochemical immunosensor based on gold nanoparticles functionalized cysteamine‐glutaraldehyde (AuNPs‐CysA‐GA) and it successfully designed to detection of the CEA biomarker in a human plasma sample. The AuNPs‐CysA‐GA provides a large surface area for the effective immobilization of CEA antibody, as well as it ascertains the bioactivity and stability of immobilized CEA antigens. Biotinylated‐anti‐CEA antibody (Ab1) was immobilized on the surface of glassy carbon electrode (GCE) modified AuNPs‐CysA‐GA. Also, secondary antibody (HRP‐Ab2) was costed immobilized to complete the sandwich part of immunosensor. Field emission scanning electron microscope (FE‐SEM and EDS), was employed to monitor the sensor fabrication procedure. The immunosensor was used for the detection of CEA using differential pulse voltammetry (DPVs) technique. The proposed interface led to enhancement of accessible surface area for immobilizing high amount of anti‐CEA antibody, increasing electrical conductivity, boosting stability, and biocompatibility. Finally, the low limit of quantitation (LLOQ) of the proposed immunosensor was obtained as 7 ng/mL with the linear range of 0.001‐5 μg/L. The proposed immunoassay was successfully applied for the monitoring of the CEA in unprocessed human plasma samples. Obtained results paved that the proposed bioassay can be used as a novel bioassay for the clinical diagnosis of cancer based on CEA monitoring.